2009
DOI: 10.1039/b816383a
|View full text |Cite
|
Sign up to set email alerts
|

High throughput single molecule detection for monitoring biochemical reactions

Abstract: The design, performance and application of a novel optical system for high throughput single molecule detection (SMD) configured in a continuous flow format using microfluidics is reported. The system consisted of a microfabricated polymer-based multi-channel fluidic network situated within the optical path of a laser source (λex = 660 nm) with photon transduction accomplished using an electron-multiplying charge coupled device (EMCCD) operated in a frame transfer mode that allowed tracking single molecules as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…The system demonstrated a sample throughput of 2208 molecules per second with a theoretical capacity of 1.7 × 10 7 molecules per second, although inefficiencies in the optical set-up made the detection of single fluorophores with this system impossible. The same group later refined this system to allow detection of singly labeled DNA molecules [6]. The principle refinements of this work included use of an electron-multiplying CCD operated in frame transfer mode and a wide field epi-illumination fluorescence system.…”
Section: Optical Detection Methodsmentioning
confidence: 99%
“…The system demonstrated a sample throughput of 2208 molecules per second with a theoretical capacity of 1.7 × 10 7 molecules per second, although inefficiencies in the optical set-up made the detection of single fluorophores with this system impossible. The same group later refined this system to allow detection of singly labeled DNA molecules [6]. The principle refinements of this work included use of an electron-multiplying CCD operated in frame transfer mode and a wide field epi-illumination fluorescence system.…”
Section: Optical Detection Methodsmentioning
confidence: 99%
“…Parallel microchannels with multiple inlets and a single outlet were shown to create a multi-laminar flow system, and each laminar flow stream could be delivered to the desired location in the jointing channel by varying the flow velocity combinations for molecular patterning [65]. Okagbare et al demonstrated that as many as thirty parallel microchannels can be fabricated within the large field-of-view under widefield illumination for the simultaneous monitoring of single-molecule biochemical reactions [66].…”
Section: Smd In Integrated Microfluidic Devicesmentioning
confidence: 99%
“…For 30 mm wide microfluidic channels, the multiplexing power (the number of different mRNAs that can be detected in a single run) would be 30 [80].…”
Section: Rt-ldr/spfret Assaymentioning
confidence: 99%